Avaliação da eficácia de sinvastatina 20 mg comprimidos e cápsulas em relação aos comprimidos referência - Flavia Dias Marques Marinho (2012)
Simvastatin (SIM), hypolipidemic worldwide used in the treatment of hypercholesterolemia (low density lipoprotein, LDLc 160 mg/dL) or mixed hyperlipidemia (LDLc 160 mg/dL and triglycerides, TG 150 mg/dL) is available as tablets (generic, similar, reference) at SUS, a Brazilian public health system and drugstores, and as capsules (compounding pharmacies). The therapeutic efficacy of the similar medicine (coated tablets) and of the compounded capsule compared to the reference medicine is assessed in 96 volunteers after checking their quality by means of physical tests (disintegration, weight determination) and of the high performance liquid chromatography for the quantification of the drug in other tests (assay, content uniformity, dissolution test). Furthermore, it is appropriate for use in dissolution studies of SV 20 mg tablets (similar and reference medicines, under controlled temperature) and capsules. All medications administered to volunteers (32 per treatment group) for 8 weeks present satisfactory quality above the minimum requirement. Only the similar tablets (SUS) show percent average dissolution efficiency statistically not homogeneous compared to the reference tablets. The reduction of LDLc levels (p >0.76) and total cholesterol (p >0.35) in volunteers (at least 93.7% in each group presents adhesion 80% to treatment) does not differ for similar tablets or capsules relative to the reference tablets. There is no significant elevation in high density lipoprotein cholesterol (HDLc) levels in the groups of treatment (p >0.05). Changes in levels of hepatic enzymes and creatine kinase did not differ between groups of treatment, so that any of the medicines may be suggested in the clinic and the choice is left to the doctor and patient